2003
DOI: 10.1073/pnas.1832434100
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall arabinan is essential for guard cell function

Abstract: Stomatal guard cells play a key role in the ability of plants to survive on dry land, because their movements regulate the exchange of gases and water vapor between the external environment and the interior of the plant. The walls of these cells are exceptionally strong and must undergo large and reversible deformation during stomatal opening and closing. The molecular basis of the unique strength and flexibility of guard cell walls is unknown. We show that degradation of cell wall arabinan prevents either sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
236
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(255 citation statements)
references
References 24 publications
13
236
2
4
Order By: Relevance
“…Eliminating side chains would then increase these associations and stiffen the wall, as indicated for arabinan side chains by Jones et al (2003) for stomatal guard cell walls, and as our previous experiments suggested (Ulvskov et al, 2005). Wild-type component(s) with t values approximately 1,000 s would, in T13.1, have become immobile enough that their relaxation lies beyond the upper t limit of our spectrum's reliable range.…”
Section: Rheological Changes In Tissues With Modified Wall Polymersmentioning
confidence: 51%
See 1 more Smart Citation
“…Eliminating side chains would then increase these associations and stiffen the wall, as indicated for arabinan side chains by Jones et al (2003) for stomatal guard cell walls, and as our previous experiments suggested (Ulvskov et al, 2005). Wild-type component(s) with t values approximately 1,000 s would, in T13.1, have become immobile enough that their relaxation lies beyond the upper t limit of our spectrum's reliable range.…”
Section: Rheological Changes In Tissues With Modified Wall Polymersmentioning
confidence: 51%
“…This suggests that the removal of arabinan side chains from RG-I backbones in T7.2 may have increased, by some 10-to 100-fold, the viscous resistance that retards the movement of some wall component(s). If this component were RG-I itself, this would diverge from the above-mentioned expectation that side groups tend to restrict backbone mobility, but it would agree with the conclusion of Jones et al (2003Jones et al ( , 2005 that removing arabinans stiffens stomatal guard cell walls.…”
Section: Rheological Changes In Tissues With Modified Wall Polymersmentioning
confidence: 76%
“…The Cnr tomato mutant shows a disrupted deposition of (1/5)-a-L-arabinan, a modified HG network with reduced calcium-binding capacity in the middle lamellae, and a reduced cell adhesion concomitant with a failure to swell (Orfila et al, 2001(Orfila et al, , 2002. A similar phenomenon is observed in the arabinan-rich walls of Commelina guard cells, in which the wall shape can be frozen open or closed by digestion of 5-linked arabinans (Jones et al, 2003). Cell walls from the Cnr mutant contain larger amounts of galactosyl-and arabinosylrich polysaccharides tightly bound in the cell wall.…”
Section: Discussionmentioning
confidence: 72%
“…Hydrolysates were resuspended in 200 μL of water. Monosaccharide analysis of the TFA treated pretreatment liquor (1 mL) was performed by high performance anion-exchange chromatography (HPAEC) (Dionex IC 3000) on a Dionex Carbopac PA-20 column with integrated amperometry detection [15]. The separated monosaccharides were quantified using external calibration with an equimolar mixture of nine monosaccharide standards (arabinose, fucose, galactose, galacturonic acid, glucose, glucuronic acid, mannose, rhamnose and xylose), which were subjected to TFA hydrolysis in parallel with the samples.…”
Section: Total Sugar Content In Pretreatment Liquorsmentioning
confidence: 99%